A Ladder Approach to Criminalising Revenge Pornography. (February 2019) - Crofts, Thomas; Kirchengast, Tyrone
The ability to distribute private intimate images across public networks including social media through smart devices or computers has emerged as a serious 21st century concern. Initially, legal systems and operators within criminal justice systems were slow to respond to the reported harms associated with the non-consensual distribution of intimate images (colloquially referred to as revenge porn). However, increasing recognition of the serious harm and victimisation that may result from this behaviour has led many jurisdictions across the world to create new criminal offences. This article reviews the appropriateness of offences that have been created or proposed with a particular reference to developments in Australia. It takes the most recent proposed offence in Western Australia as an opportunity to review the significant differences in how offences have been defined. In suggesting how new offences might be defined, this article relies on the 'ladder principle' and recommends that there should be a ladder or hierarchy of new offences to respond appropriately to both the seriousness of harm and culpability of the perpetrator.